Cytological identification of Blastocystis hominis in the ascites of a patient with rectal carcinoma: a case report - Lin, Qian; Huang, Jun; Chen, Yuanyuan; Wu, Xiaoli; Ma, Yuhua; Yang, Qing; Long, Pan; Chen, Xin (Frontiers in Medicine, 2025)
IntroductionBlastocystis hominis (B. hominis), a protozoan parasite often found in the human intestinal tract, is typically identified through fecal examination. Its presence in ascitic fluid is quite uncommon, making such a detection significant in the context of medical diagnosis.Case presentationIn this case report, we describe a 53-year-old female patient who presented with a 6-month history of recurrent diarrhea and fecal incontinence subsequent to the diagnosis of rectal signet ring cell carcinoma. The patient was discovered to have a severe abdominal infection, with B. hominis identified in both the abdominal cavity and the intestinal tract. Marked improvement in diarrheal symptoms was achieved following peritoneal lavage with metronidazole.ConclusionThis case underscores the significance of detecting B. hominis infection in the ascitic fluid of a patient afflicted with rectal signet ring cell carcinoma. B. hominis, a prevalent opportunistic pathogen, often exploits the compromised immune states and nutritional deficiencies prevalent in cancer patients, rendering them more susceptible to such infections. It is imperative to enhance diagnostic accuracy and mitigate the risk of misdiagnosis to subsequently improve the clinical outcomes and overall quality of life for individuals battling cancer.